2019
DOI: 10.1109/access.2019.2952468
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and Application of Hybrid Firefly Algorithm

Abstract: Aiming at the problem of poor global search ability and slow convergence speed when solving optimization problems, this paper proposes improved hybrid firefly algorithm (HFA). HFA improves the position updating method, mutation strategy, chaotic search method and evolution strategy of the population. Specifically, the improved position update formula considers both the effect of high-brightness fireflies on position-updated fireflies, and the effects of the optimal firefly on position-updated fireflies. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Levy flight can be used to control firefly movement. The random step length, drawn from a Levy distribution, is shown in ( 35) [43].…”
Section: Imentioning
confidence: 99%
“…Levy flight can be used to control firefly movement. The random step length, drawn from a Levy distribution, is shown in ( 35) [43].…”
Section: Imentioning
confidence: 99%
“…Yang created the Firefly Algorithm (a revolutionary swarm intelligent optimization scheme) in 2008, after analyzing the movement mechanism and mutual attraction of firefly individuals (FA). Because, the Firefly Algorithm has the benefits of a basic concept, ease of deployment, less parameter impact on the method, and fewer parameters to specify [41]. As a result, the firefly algorithm is a heuristic method designed to mimic the biological properties of adult insect luminescence in the environment.…”
Section: Firefly Optimization Algorithmmentioning
confidence: 99%
“…It was also observed that the experimentations showed an enhanced accuracy rate in terms of classification rather than compared ones. Wang et al [57] has proposed a collective mutation function into an enhance HFA, to efficiently consider the local as well as global search capabilities for resolving the optimization issues. As chaotic search (CS) reveals superior ergodicity, an evolution approach for arbitrary association of all fireflies according to CS was introduced, that improves the algorithm capability to negotiate the overall search space.…”
Section: Hybridized Firefly Algorithm (Hfa)mentioning
confidence: 99%